Indicators For Arabic Language Lecturers’ Competencies in Universiti Teknologi Mara on Teaching Effectiveness: A Hybrid PLS-SEM Modelling Approach - Mazlan, Nurul Asma; Arifin, Zamri; Zailani, Suhaila; Norwahi, Nur Aqilah; Saad, Mohd Faizulamri Mohd; Nordin, Mohd Norazmi; Jaafar, Mohd Arafat (CENTRAL ASIA AND THE CAUCASUS, 2022)
Partial Least Squares Structural Equation Modelling (PLS-SEM) has gained acceptance as the 2nd generation multivariate statistical procedure for education research in recent years. Although there is a growing amount of literature utilizing this statistical procedure, researchers may still find reporting PLS-SEM results and designing advanced models difficult. The aim of this study is to determine Arabic language lecturers’ competencies on teaching effectiveness using Smart PLS software. Based on the descriptive analysis, the results revealed that majority of the respondents were female, single, aged between 22-24 years old and currently study at degree’s level. Additionally, most of the respondents were students from Faculty of Business and Management at Universiti Teknologi MARA (UiTM), Melaka Campus. Referring to the correlation analysis, the finding discovered that there is a positive and strong relationship between Arabic language lecturers’ competencies on teaching effectiveness. In fact, e-learning tools also play an important role in influencing lecturers’ competencies and affect teaching effectiveness. It can be summarized that, the indicators developed can measure the effectiveness of lecturers’ teaching sessions and it can also be used as a benchmark (parameter) to Arabic language lecturers in other universities.